2017
DOI: 10.1089/gtmb.2016.0422
|View full text |Cite
|
Sign up to set email alerts
|

Support for “Disease-Only” Genotypes and Excess of Homozygosity at the CYTH4 Primate-Specific GTTT-Repeat in Schizophrenia

Abstract: This indicates that STR genotypes that are absent in the control group may be risk factors for SCZ. Future studies are warranted to test the significance of our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Recent findings of a link between the low-frequency alleles at the extreme short and long ends of "exceptionally long" STRs with human disorders [5][6][7] Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings of a link between the low-frequency alleles at the extreme short and long ends of "exceptionally long" STRs with human disorders [5][6][7] Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that approximately 2% of the human protein-coding genes contain STRs of ≥6 repeats in the critical core promoter region [3]. Preliminary findings indicate that expansion of a number of these STRs may be linked to adaptive evolutionary processes in human, and also endure the burden of certain human disorders such as schizophrenia, bipolar disorder, and Alzheimer's disease [4][5][6][7].…”
Section: Introductionmentioning
confidence: 93%
“…A number of the identified STRs such as GTTT have established repressor activity [ 6 , 28 , 29 ] and are differentially expanded in certain genes in the Old World monkeys and Apes [ 14 ]. Purine STRs such as GAAA repeats are also functional in gene expression regulation, and their link to certain diseases unique to humans were previously reported [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human specificity of the predominant allele of the RIT2 core promoter STR in the human species, the presence of the shortest allele of this STR (5-repeat) in hunter-gatherer humans (BUSHMAN KB1: rs113265205), the lack of this allele in the agricultural modern humans (Genome Aggregation database: gnomad.broadinstitute.org ), and its co-occurrence with schizophrenia provide the first indication of STR allele selection in humans [ 13 ]. A link between the CYTH4 core promoter STR (the longest tetranucleotide STR identified in a human gene core promoter) with the Old World monkeys and Apes and evidence of extreme “disease-only” genotypes at this STR with schizophrenia [ 14 ] provide the first link between a primate-specific STR and higher-order brain functions in human. The “exceptionally long” CA-repeat in the core promoter of SCGB2B2 is another example of directional STR expansion in the Old World monkeys and Apes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-scale findings of the evolutionary trend of a number of STRs has begun to unfold their implications in respect with speciation and species-specific characteristics/phenotypes (Yuan et al 2018;Emamalizadeh et al 2017;Abe and Gemmell 2016;Bushehri et al 2016;Namdar-Aligoodarzi et al 2016;Nikkhah et al 2016;Bilgin Sonay et al 2015;Rezazadeh et al 2014;Khademi et al 2017;Mohammadparast et al 2014;Ohadi et al 2012;King et al 2012). The hypermutable nature of STRs and their large unascertained reservoir of functionality make them an ideal source of evolutionary adaptation, speciation, and disease (Hannan et al 2018;Bagshaw et al 2017;Press et al 2017;Ohadi et al2015;Valipour et al 2013;Heidari et al 2012).…”
Section: Introductionmentioning
confidence: 99%